Analisis Model Evaluasi Program Pendidikan Karakter Islami Pada Satuan Pendidikan Tingkat SD di Kabupaten Pidie Jaya - Mukhlis Mukhlis; Djaman Satori; Eka Prihatin; Suryadi Suryadi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to analyze the implementation of the Islamic character education program in elementary schools in Pidie Jaya Regency using the CIPP evaluation model (Context, Input, Process, Product) to determine its effectiveness, readiness, and the challenges encountered in shaping students’ character. Applying a qualitative evaluative approach, data were collected through observations, in-depth interviews with the education office, school principals, teachers, and community leaders, as well as documentation studies of curricula, assessment instruments, and school activity programs. The findings indicate that in terms of context, the program is strongly supported by local government regulations and the religious culture of the community. In the input component, teacher competence in integrating Islamic character values into learning and the availability of facilities such as prayer rooms, libraries, and character-building spaces vary significantly among schools, influencing program quality. Regarding the process, religious habituation activities such as congregational prayer, Qur’an recitation, and moral guidance are implemented well, although the integration of character values into classroom learning remains inconsistent. In the product component, the program demonstrates positive impacts on students’ behavior, but its effectiveness is hindered by digital exposure, limited parental supervision, and uneven implementation across schools. The study concludes that the program is moderately effective but requires strengthening in teacher capacity, facility provision, and collaboration among the three centers of education: school, family, and community. Recommendations include continuous teacher training, development of adequate supporting facilities, enhancement of digital literacy and supervision, and the establishment of a more systematic and sustainable evaluation mechanism for program improvement. Keywords: Islamic Character Education; CIPP Model; Elementary Schools; Program Evaluation Abstrak: Penelitian ini bertujuan untuk menganalisis pelaksanaan program pendidikan karakter Islami pada satuan pendidikan tingkat sekolah dasar di Kabupaten Pidie Jaya dengan menggunakan model evaluasi CIPP (Context, Input, Process, Product) guna mengetahui efektivitas, kesiapan, dan hambatan program dalam membentuk karakter peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian evaluatif melalui teknik observasi, wawancara mendalam dengan dinas pendidikan, kepala sekolah, guru, serta tokoh masyarakat, dan studi dokumentasi terhadap kurikulum, instrumen penilaian, serta program kerja sekolah. Hasil penelitian menunjukkan bahwa dari aspek konteks, program memiliki landasan kebijakan yang kuat melalui Peraturan Bupati serta dukungan budaya masyarakat yang religius. Pada aspek input, ditemukan bahwa kompetensi guru dalam mengintegrasikan nilai karakter Islami serta ketersediaan sarana prasarana seperti mushalla, perpustakaan, dan fasilitas pembinaan akhlak masih belum merata sehingga memengaruhi kualitas implementasi program. Pada aspek proses, kegiatan pembiasaan religius seperti salat berjamaah, tadarus, dan pembinaan akhlak berlangsung baik, tetapi integrasi nilai karakter ke dalam pembelajaran masih belum konsisten di semua sekolah. Pada aspek produk, program memberi dampak positif terhadap perilaku siswa meskipun belum optimal karena adanya pengaruh digitalisasi, rendahnya pengawasan orang tua, dan variasi penerapan antar sekolah. Simpulan penelitian menegaskan bahwa program telah berjalan cukup efektif namun membutuhkan penguatan pada kompetensi guru, fasilitas pendukung, dan sinergi tripusat pendidikan. Saran penelitian meliputi peningkatan pelatihan guru, pengembangan sarana prasarana, penguatan literasi digital, serta evaluasi program yang lebih sistematis dan berkelanjutan. Kata kunci: Pendidikan Karakter Islami; Model CIPP; Sekolah Dasar; Evaluasi Program